Development, Characterization And Optimization Of Solid Lipid Nanoparticles Of Clarithromycin By Box-Behnken Design Approach - Dhanaraju, Magharla Dasaratha; Sundar, Vankayala Devendiran; Vadaga, Anilkumar; Durga, Seeram Kalyani (Journal of Neonatal Surgery, 2025)
The present study focuses on the application of Quality by Design (QbD) in the formulation and optimization of Clarithromycin-loaded Solid Lipid Nanoparticles (SLNs) to enhance bioavailability and therapeutic efficacy. Clarithromycin, a macrolide antibiotic, has poor aqueous solubility and stability issues, limiting its therapeutic potential. SLNs, composed of Glyceryl Monostearate (GMS) as the lipid carrier and Poloxamer 188 as the surfactant, were developed using high-shear homogenization and probe sonication techniques. A Box-Behnken Design (BBD) was employed to evaluate the effect of drug: lipid ratio, surfactant concentration, homogenization speed, and sonication time on critical quality attributes such as particle size, entrapment efficiency, and in vitro drug release. The optimized formulation (F6) exhibited controlled drug release with higher entrapment efficiency (85.0 ± 0.8%) and reduced particle size (180.0 ± 1.2 nm). FTIR and DSC studies confirmed no drug-excipient interactions, ensuring formulation stability. In vitro drug release studies demonstrated sustained release over 24 hours compared to the marketed formulation. Stability studies as per ICH guidelines confirmed that the formulation remained stable for three months without significant changes in particle size or entrapment efficiency. The optimized SLN formulation (F6) successfully enhanced the solubility, stability, and controlled release profile of Clarithromycin, making it a promising carrier for improved oral bioavailability and targeted drug delivery.